Chemistry teachers’ self-efficacy scale for differentiated instruction: Development and validation - Rais Assad Faiz; Hari Sutrisno (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2025)
This research aims to develop and validate a new instrument for measuring chemistry teacher’s self-efficacy for differentiated instruction. Data was collected using developed questions based on a literature study. The data were analyzed using exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and correlational techniques based on responses from 156 chemistry teachers in Yogyakarta who participated in an offline and online survey. The findings from EFA, CFA, and correlation analysis provide sufficient empirical evidence to support the convergent and discriminant validity of the instrument. The high Cronbach’s coefficient alpha values show the instrument’s good internal consistency and reliability. We documented a valid and reliable chemistry teachers’ self-efficacy for differentiated instruction with six constructs consisting of 22 items by integrating the evidence from theory and data. The six-factor scale is named